A Guide to Implementation Science for Phase 3 Clinical Trialists: Designing Trials for Evidence Uptake - Van Spall, Harriette; Desveaux, Laura; Finch, Tracy; Lewis, Cara C.; Mensah, George A.; Rosenberg, Yves; Singh, Kavita; Venter, Francois; Weiner, Bryan J.; Zannad, Faiez (Journal of the American College of Cardiology, 2024)
The delayed and modest uptake of evidence-based treatments following cardiovascular clinical trials highlights the need for greater attention to implementation early in the development and testing of treatments. However, implementation science is not well understood and is often an afterthought following phase 3 trials. In this review, we describe the goals, frameworks, and methods of implementation science, along with common multilevel barriers and facilitators of implementation. We propose that some of the approaches used for implementation well after a trial has ended can be incorporated into the design of phase 3 trials to foster early post-trial implementation. Approaches include, but are not limited to, engaging broad stakeholders including patients, clinicians, and decision-makers in trial advisory boards; using less restrictive eligibility criteria that ensure both internal validity and generalizability; having trial protocols reviewed by regulators; integrating trial execution with the health care system; evaluating and addressing barriers and facilitators to deployment of the intervention; and undertaking cost-effectiveness and cost utility analyses across jurisdictions. We provide case examples to highlight concepts and to guide end-of-trial implementation.
Gesehen am 20.08.2024